Enhanced performance of P3HT/(PCBM:ZnO:TiO2) blend based hybrid organic solar cells. (March 2016) - Ikram, M.; Murray, R.; Imran, M.; Ali, S.; Shah, S.Ismat
Graphical abstract: Highlights: We fabricated hybrid bulk heterojunction organic solar cells. TiO2 and ZnO nanoparticles replace PCBM with fixed amount of P3HT in active layer PCE was significantly improved by the introduction of TiO2 and ZnO. A possible route toward low-cost OPV. To the best of my knowledge, this work is the first time going to report. Abstract: Quaternary blend hybrid organic solar cells enjoy both an increased light absorption range and an easy method to fabricate because of the simple structure. In this study effects of mixing inorganic metal oxides (ZnO and TiO2 ) nanoparticles to the active layer of organic photovoltaics devices were investigated. The active layer primarily consists of various ratios of electron donor poly (3-hexylthiophene) (P3HT) and an electron acceptor [6, 6]-phenyl-C61-butyric acid methyl ester (PCBM) together with nanostructured ZnO and TiO2 dispersed in chlorobenzene (CB) and 1, 2-dichlorobenzene (DCB). The ratio of PCBM to nanoparticles was varied keeping the ratio of P3HT to acceptor material constant. Mixing of nanoparticle plays a significant role in the resulting power conversion efficiency (PCE) of the devices. An increased PCE for ZnO/TiO2 doped devices can be attributed to increased absorption in the visible region and enhanced charge collection due to the percolation networks formed by metal oxides nanoparticles.